1987
DOI: 10.1029/jc092ic12p13013
|View full text |Cite
|
Sign up to set email alerts
|

Satellite passive microwave studies of the Sea of Okhotsk ice cover and its relation to oceanic processes, 1978–1982

Abstract: This paper describes the use of the Nimbus 7 Scanning Multichannel Microwave Radiometer (SMMR) satellite data to study the ice cover in the Sea of Okhotsk during the four winters of 1978-1982. The ice concentration estimates obtained from SMMR are used to study two different polynyas: one over the Kashevarova Bank, and the other over the northwest continental shelf. For the Kashevarova polynya this study shows that the polynya, which may be related to the upwelling observed in historic summer cruises, occurs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 19 publications
1
66
0
Order By: Relevance
“…Two potential source regions of NPIW have been proposed: the Sea of Okhotsk outflow (Wust, 1930;Kitani, 1973;Alfultis and Martin, 1987;Talley, 1991;Talley and Nagata, 1995;Yasuda, 1997); and the Gulf of Alaska (Van Scoy et al, 1991;You et al, 2000). The latter has received less attention in recent years; as Van Scoy et al (1991) admitted, waters of 26.8 σ θ have never been observed at the surface in the Alaskan Gyre.…”
Section: B North Pacific Intermediate Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Two potential source regions of NPIW have been proposed: the Sea of Okhotsk outflow (Wust, 1930;Kitani, 1973;Alfultis and Martin, 1987;Talley, 1991;Talley and Nagata, 1995;Yasuda, 1997); and the Gulf of Alaska (Van Scoy et al, 1991;You et al, 2000). The latter has received less attention in recent years; as Van Scoy et al (1991) admitted, waters of 26.8 σ θ have never been observed at the surface in the Alaskan Gyre.…”
Section: B North Pacific Intermediate Watermentioning
confidence: 99%
“…The Kashevarov Bank is a site of intense heat loss and hence dense water formation (Alfultis and Martin, 1987) related to the strong upwelling and vertical mixing discussed by Suzuki and Kanari (1986). With much dispute as to whether dense water is produced in sufficient quantities to form NPIW, Alfutis and Martin (1987) focused on estimating the magnitude of this OIW production through an estimation of the production of dense shelf water.…”
Section: Formation Of Okhotsk Intermediate Watermentioning
confidence: 99%
“…Therefore, sea ice transports negative heat and negative salt from north to south. Salt rejection due to active sea ice formation in the polynyas over the northern and northwest shelf produces Dense Shelf Water, which is regarded as a ventilation origin of North Pacific Intermediate Water (NPIW) (Alfultis and Martin 1987).…”
Section: Introductionmentioning
confidence: 99%
“…It showed that the heat fluxes over open water area are two orders of magnitude greater than those over the sea ice. For the Okhotsk coastal polynyas, Alfultis and Martin (1987) and Martin et al (1998) calculated the net surface heat flux by the bulk method to investigate ice and brine production in the polynyas. All these heat flux estimates are confined to a limited region; the surface heat flux for the entire Okhotsk Sea has not been estimated on the basis of observed data.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Sea is geographically located at a temperate latitude, it has many characteristics of a polar ocean, namely, large seasonal variation in water temperatures (~14°C) and large amounts of sea ice along the Siberian coast over the northwestern continental shelf of the east coast of Sakhalin Island every winter (Alfultis & Martin 1987). The Sea of Ohkotsk is recognized as the most productive marine basin amongst the world's oceans (Sorokin & Sorokin 1999).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%